Enhancing Arabic Reading Proficiency as a Second Language: Unveiling the Significance of Audiobooks for Middle School Students - SAAD, HEBA ABDALLA AMIN (2024)
Purpose- The use of digital tools and platforms in language classrooms has become a crucial pedagogical strategy. The integration of technology has significantly changed the landscape of foreign language education, enhancing both teaching and learning experiences. Considering audiobooks as a useful tool in improving reading skills and language acquisition, this study aims to explore the potential benefits and effectiveness of using audiobooks as a tool for learning for non-Arab students in Dubai, as there is a diverse student population including individuals from various cultural and linguistic backgrounds which can present significant challenges. It also discusses the pedagogical philosophy of how teachers and students use this tool, identifies the obstacles to the appropriate use of audiobooks in Middle Schools in Dubai, and lastly, make suggestions about how to get through these obstacles. Methodology- Both qualitative and quantitative approaches were employed to collect the study's data. Eleven Arabic teachers from different Dubai schools participated in this qualitative study to determine the significance of audiobooks for non-native Arabic speakers enrolled in Dubai middle schools. The quantitative investigation included a questionnaire. 111 parents who have children enrolled in middle schools in Dubai answered the questionnaire that was sent to them. The questionnaire's main objectives are to validate the findings of the interviews and to ascertain the parents' opinions regarding the value and efficacy of audiobooks as a teaching tool among Dubai's non-Arab student population and the potential effects this may have on middle school students' reading skills. Findings- The analysis of data revealed that the good application of Audiobooks in Dubai schools is yet to be accomplished. Audiobooks have emerged as a promising tool for enhancing reading skills and language acquisition. They provide learners with an immersive and interactive experience, combining oral and written language comprehension. Audiobooks have been found to improve pronunciation, fluency, and comprehension skills. Implications- One significant implication is the need to examine the correlation between audiobooks and the curriculum and to raise awareness about it and its importance in the schools. The study also makes some recommendations to integrate cross-curricular connections between the subjects being studied and the language content, thereby enhancing the overall meaningfulness of the learning experience for the students. Originality/ value- This study provides new insights at both practical and scholarly levels. The findings of this study can provide valuable insights into the effectiveness of audiobooks as a supplementary tool in Arabic language instruction. This can contribute to the development of more comprehensive and innovative teaching approaches that cater to the diverse learning needs of Arabic foreign learners. Moreover, it can help educators and language instructors make informed decisions regarding the integration of audiobooks into their teaching practices. By understanding the benefits and limitations of audiobooks, instructors can effectively incorporate them into their curriculum, thereby promoting a more engaging and interactive learning environment for Arabic language learners. Keywords: Arabic reading skills, E-books, audiobooks.